Prevalence of Panton-Valentine Leukocidin Staphylococcus aureus among Patients and Healthcare Workers in Malaysian Public Hospital - Samsudin, Syahirah; Al-Talib, Hassanain; Mohd-Zain, Zaini; Al-Khateeb, Alyaa; Dalila Mohamad Ali, Norliana; ., . (International Journal of Engineering and Technology, 2018)
Staphylococcus aureus carrying Panton-Valentine leukocidin (PVL) has become a worldwide threat to public health. Recent reports showed an increasing numbers of Staphylococcus aureus infections caused by PVL-positive organisms worldwide which explain the need to carry out this study in Malaysia. The objective of this study was to determine the prevalence of PVL-positive Staphylococcus aureus among patients and healthcare workers in Malaysian Public Hospital. Collectively, 230 swabs were collected from the anterior nares of inpatients and healthcare workers at Sungai Buloh Hospital. The isolates were identified and characterized using conventional and molecular methods. From 230 samples collected, 23% (53/230) were detected as Staphylococcus aureus isolates. Out of the 53 Staphylococcus aureus isolates, 2 (3.8%) were found to be PVL-positive Staphylococcus aureus (from patientâ€™s sample) and the remaining 51 (96.2%) isolates were PVL negative Staphylococcus aureus. Out of 53 Staphylococcus aureus isolates, 40 (75.5%) were methicillin-sensitive and 13 (24.5%) were methicillin-resistance Staphylococcus aureus. The finding of the prevalence of PVL-positive Staphylococcus aureus among patients and healthcare workers will provide awareness to the hospital authority to take action for prevention and control.Â Â